Effect of ethylene inhibitors in extending the vase life of camation idianthus caryophyllus l.) cut flowers as substitutes of silver thiosulfate (sts) (2001)
In Colombia the sector of cut flower exportation has greateconomic importance. However, high production costs and lowprices have reduced the profitability off flowers in the last years. With the objective of compared the response of traditional products in postharvest, whose main ingredient is the Ag+ ion, with other products of more degradability, a research was carried out with standard carnation variety 'Nelson'. The floral stalks were harvested in a crop under greenhouse conditions in a commercial production farm ofthe Bogotá plateau. Flowers were graded and treated with different postharvest solutions in order to pro long vase life. Later on, they were kept in simulated transport conditions during a period of ten days; then, postharvest measurements were made in the Laboratory of Plant Physiology of the National University of Colombia, Bogotá. In the laboratory stems were kept in distilled water, under photoperiod conditions of 12 h (artificial light from 6 a.m. to 6 p.m.) and with ventilation of 30 min in the morning hours to avoid ethylene accumulation. Environmental conditions of the laboratory were 19°C and relative humidity of 75%. The commercial preservative products used were: Silver Thiosulfate (STS) elaborated in the farm, 1- Methylcyclopropene (I-MCP), Chrysal AVB, Chrysal EVB,Florissima 125, Florissima 135 and Florissant 100. The bestresults in florallongevity were obtained with the combinationof l-MCP + Florissima 135 (22 days), Florissima 125 (21,7 days) and STS (21,5 days). It was proven that sorne products that not contain the Ag ' ion (Florissima 135 and Chrysal EVB)presented similar results as compared to the compounds thatcontained the Ag+ ion. Therefore, Florissima 135 and ChrysalEVB can be efficient in the substitution of STS which ispotentially an environmental pollutant.